Analysis of Accounting Perceptions and Knowledge in The Implementation of Private Entity Account (EP) in The Preparation of Financial Reports - Kamil, Islamiah; Yolifiandri, Yolifiandri; Irawan, Indra Ade; Watriningsih, Watriningsih; Ariani, Meiliyah (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This study aims to explore the perceptions and accounting knowledge of cooperative business actors regarding the implementation of Financial Accounting Standards for Private Entities (SAK EP) in preparing financial reports. SAK EP is an accounting standard designed specifically for private entities without public accountability to guide the preparation of cooperative financial reports. The research employed a survey method, utilizing questionnaires distributed to cooperative business actors in the Jakarta, Bogor, Depok, Bekasi, and Tangerang (Jabodetabek) areas, who are directly involved in preparing financial reports for private entities. The collected data were examined using descriptive statistical techniques and regression analysis through Smart PLS software to identify the relationships between the studied variables. The findings are expected to provide insights into the level of perception and accounting knowledge related to SAK EP among cooperative business actors in the Jabodetabek area. These results could serve as a foundation for the government, regulators, and other stakeholders to enhance the understanding and application of these accounting standards. Additionally, this research aims to contribute to the academic literature concerning the implementation of financial accounting standards in private entities.